ANALYSIS OF THE ROLE OF SYNONYMS IN TEACHING ENGLISH AND THEIR DIFFERENCES (Scientific Conference on Multidisciplinary Studies, 2025)
Synonyms empower learners to be more discerning in their word choices. Understanding the subtle distinctions between synonyms helps students select the most precise and contextually appropriate term for conveying their intended meaning. Teaching the art of word choice encourages learners to be mindful of the impact their language can have, promoting clarity and avoiding ambiguity. Engaging with synonyms stimulates cognitive processes as learners navigate through the similarities and differences between words. This cognitive exercise contributes to mental flexibility and linguistic dexterity. The mental effort involved in discerning between synonyms enhances critical thinking skills, as learners must evaluate the nuances and select the word that best fits a specific context. Synonyms often carry cultural and contextual nuances.